Neurobiologia da Aprendizagem Escolar: difusão de conhecimentos sobre Neurociência aplicada à Educação - Lupi Júnior, Luiz Antonio [UNESP] (2015)
The university project, "Neurobiology of School Learning: diffusion of Neuroscience knowledge applied to Education”, has the elementary and high school communities, teachers and students, as well as future teachers as target public. The project promotes discussion, at different levels, about issues such as learning, memory and attention. The knowledge of these subjects has increased in Neurobiology and it is of great interest to the school. Even considering the correlation between Neurobiology and Education, there are difficulties to find an interface, due to different methods, goals, approach levels and languages. This university outreach project, supported by PROEX, was based on the diagnosis with the participants regarding their interest and level of knowledge on the issues. The project consists of actions aimed at the diffusion and popularization of Neurobiology knowledge applied to school learning. The actions take place in a fun and attractive way, both for the teacher and for the student of basic education system in Botucatu region. Through different interactive actions, we realized that the relationship between University and Basic Education School is an enriching and important experience to minimize conceptual distortions about Neurobiology of learning and to contribute to the continuous training of educators, in both fields.